Lived experiences in end-of-life care and acceptability of advance health care directives in a highly educated urban sample - Villaseñor, Irene Manese
In-depth face-to-face interviews using semi-structured and open-ended questions were conducted to understand the decision making processes experienced by 15 individuals in the end-of-life care of 16 immediate family members (IFMs). Carers were mostly females, married, Catholics, college- and postgraduates, and employed. The family closeness and solidarity of the carers and their IFMs were apparent. Our Collectivist culture, however, enhanced the perceived autonomy of IFMs. As recounted by their carers, all IFMs were actively involved in their health care and gave their informed consent regarding all possible medical treatments to delay the progression of their chronic illnesses. For some carers, however, discussions of preferences did not continue as the illness became deemed terminal. All carers' end-of-life decisions were based on substituted judgment or best interest criteria. Eleven IFMs died, either at home or in the hospital, without extraordinary interventions. Two died with respiratory support against their verbal preferences. IFMs who had longer history of last illness, of being bedridden, of becoming bedridden prior to their last hospitalizations, and of having poor prognosis were not given artificial interventions. Concepts of autonomy, quality of life, and good death were then clarified and linked to the carers' retrospective and prospective end-of-life decisions, and to cultural and personal acceptability of advance health care directives (AHCD). Health and wealth were mentioned in all carers' description of quality of life while togetherness is an important measure of a good life. Peace and freedom from pain described good death. Based on their experiences, most carers came to realize that the patient first then the immediately family second, in consultation with the doctor, should decide with regards to the patient's medical treatment. Most carers, in retrospect, realized the need to know their IFMs' preferences, especially pertaining to end-of-life. In their prospective end-of-life, when they are suffering from a terminal illness and with very low quality of life, most carers would opt for care rather than cure so as not to prolong imminent death, not be a burden to one's family, and for financial reasons. Majority of carers indicated the cultural acceptability of AHCD as an option in end-of-life care. Most carers were willing to write AHCD but stressed the importance of information dissemination before AHCD could be fully understood and appreciated. In the Filipino culture, the more appropriate model of AHCD is the "bottom-up" model, which emphasizes the values, needs, and goals of patients and family members. The concept of AHCD in end-of-life care is new in the Philippines and, being a legal document, a specific legislation in relation to AHCD should be enacted. AHCD may be incorporated in the Magna Carta of Patient's Right and Obligations or in an Asian model similar to the Hospice and Palliative Care Act of Taiwan. Such a low would allow information dissemination and would make it easier for the dying to ensure that end-of-life preferences are respected.